Tailoring Cu2+-loaded electrospun membranes with antibacterial ability for guided bone regeneration - Cordeiro, Jairo M. (2022)
Copper (Cu)-loaded electrospun membranes were tailored for guided bone regeneration (GBR), targeting the stimulation of innate cells active in bone growth and the prevention of bacterial infections. Functional GBR membranes were produced via an electrospinning set-up using a silk-based solution associated with polyethylene oxide (Silk/PEO - control). Experimental groups were loaded with copper oxide using varying weight percentages (0.05 % to 1 % of CuO). The morphological, structural, chemical, and mechanical properties of membranes were evaluated. Direct and indirect in vitro cytocompatibility experiments were performed with primary human bone mesenchymal stem cells and primary human umbilical vein endothelial cells. The antibacterial potential of membranes was tested with Staphylococcus aureus and Fusobacterium nucleatum biofilm. CuO was successfully incorporated into membranes as clusters without compromising their mechanical properties for clinical applicability. Increased Cu concentrations generated membranes with thinner nanofibers, greater pore areas, and stronger antimicrobial effect (p < 0.01). Cu2+ ion was released from the nanofiber membranes during 1 week, showing higher release in acidic conditions. CuO 0.1 % and CuO 0.05 % membranes were able to support and stimulate cell adhesion and proliferation (p < 0.05), and favor angiogenic responses of vascular cells. In addition, detailed quantitative and qualitative analysis determined that amount of the attached biofilm was reduced on the tailored functional Cu2+-loaded GBR membrane. Importantly, these qualities represent a valuable strategy to improve the bone regeneration process and diminish the risk of bacterial infections.